Techniques and ethics in public administration [review of] - Caoili, Olivia C. (Philippine Journal of Public Administration, 1983)
A review of Rosamund M.Thomas, The British Philosophy of Administration: A Comparison of British and American Ideas, 1900-1939 (London and New York: Longman, 1978), 280 pp. including appendix and index; text only 243 pp.